Taxonomy and nomenclature of some mainland SE-Asian Coeliccia species (Odonata, Platycnemididae) using micro-CT analysis - Steinhoff, Philip O. M.; Uhl, Gabriele (Zootaxa, 2015)
The taxonomic status of some mainland Southeast Asian Coeliccia species is evaluated. The following synonymies are presented: C. acco is a junior synonym of C. pyriformis; C. tomokunii that of C. scutellum; C.onoi that of C. cyanomelas. C. scutellum hainanense is promoted to species level, C. hainanense. Redescriptions of the holotype of C. pyriformis and of the lectotypes of C. scutellum and C. hainanense are presented with illustrations. The male genital ligulae were examined by means of non-destructive X-ray micro-computed tomography (micro-CT) and subsequent 3D-reconstruction. The advantage of virtual types generated by micro-CT analysis, particularly for the examination of internal structures, is discussed.